Overcoming the Challenges Faced by Immigrant Populations While Accessing Primary Care: Potential Solution-oriented Actions Advocated by the Bangladeshi-Canadian Community - Tanvir C Turin; Sarika Haque; Nashit Chowdhury; Mahzabin Ferdous; Nahid Rumana; Afsana Rahman; Nafiza Rahman; Mohammad Lasker; Ruksana Rashid (SAGE Publishing, 2021)
Introduction: Immigrants continue to face significant challenges in accessing primary healthcare (PHC) that often negatively impact their health. The present research aims to capture the perspectives of immigrants to identify potential approaches to enhance PHC access for this group. Methods: Focus group discussions (FGDs) were conducted among a sample of first-generation Bangladeshi immigrants who had experience with PHC in Canada. A total of 13 FGDs (7 among women, 6 among men) were conducted with 80 participants (women = 42, men = 38) in their preferred language, Bangla. We collected demographic information prior to each focus group and used descriptive statistics to identify the socio-demographic characteristics of participants. We applied thematic analysis to examine qualitative data to generate a list of themes of possible approaches to improve PHC access. Results: The focus group findings identified different levels of approaches to improve PHC access: individual-, community-, service provider-, and policy-level. Individual-level approaches included increased self-awareness of health and wellness and personal knowledge of cultural differences in healthcare services and improved communication skills. At the community level, supports for community members to access care included health education workshops, information sessions, and different support programs (eg, carpool services for senior members). Suggested service-level approaches included providers taking necessary steps to ensure an effective doctor-patient relationship with immigrants (eg, strategies to promote cultural competencies, hiring multicultural staff). FGD participants also raised the importance of government- or policy-level solutions to ensure high quality of care (eg, increased after-hour clinics and lab/diagnostic services). Conclusions: Although barriers to immigrants accessing healthcare are well documented in the literature, solutions to address them are under-researched. To improve healthcare access, physicians, community health centers, local health agencies, and public health units should collaborate with members of immigrant communities to identify appropriate interventions.